MATEO CORRALES LANTERO - Obras y proyectos de arquitectura - Mera, Juan (ZARCH, 2016)
MATEO CORRALES LANTEROObras y proyectos de arquitecturaLampreave, 2015. 208 págs, ISBN/ISSN: 978-84-608-1471-9Idioma: castellano / inglés. 35 €